Evaluasi Kesesuaian Lahan Tanaman Nilam di Desa Pantai Tinjau Kecamatan Sekerak Kabupaten Aceh Tamiang - Salsabila; Cut Mulyani; Iswahyudi (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2025)
Patchouli (Pogostemon cablin Benth) is one type of industrial plant that has the potential to be developed as one of the superior regional commodities in Aceh Tamiang district, which has so far only focused on oil palm and rubber plants. The study aimed to determine the suitability of patchouli land in Pantai Tinjau Village, Sekerak District, Aceh Tamiang Regency. The study used a survey method with descriptive analysis based on field observations and laboratory analysis with sample determination by